PELATIHAN DAN PENYULUHAN HUKUM PERJANJIAN KONTRAK JUAL BELI PADA PAGUYUBAN PERIAS PONOROGO - INDRASARI, FEBRINA; Mirza Syafitri, Eva; Kusbandono, Hendrik (JURNAL DAYA-MAS, 2018)
This community service was aimed to give understanding to Paguyuban Perias Ponorogo as an entrepreneurship group in goods and service sector of cosmetics accessory equipment about the importance of contract law of sale and purchase in business as proper contract will give legal security to the parties and can be used as legal basis for the parties. It is expected that those entrepreneurs can apply it in their business in order to get their rights law with the strong basis that can support the finance of their business. The study was conducted at Kota Ponorogo on 2 October 2017. The method that was used was giving material about contract law of sale and purchase, discussing the problems related to the previous sale and purchase agreement in Paguyupan Perias Ponorogo and training to make letter of sale and purchase agreement properly. The result of the activity shows that Paguyuban Perias Ponorogo did not know and understand about contract law of sale and purchase and the importance of letter of sale and purchase agreement in business as the agreement that they had done previously was still orally.Â Keywords: Contract law of sale and purchase, Letter of Sale and Purchase Agreement